Impact of nitroglycerin on 28-day mortality in ischemic stroke patients: a retrospective cohort study using the MIMIC-IV database - Zuo, Huan; Zuo, Xin; Wang, Linjing (Frontiers in Neurology, 2025)
BackgroundThe impact of nitroglycerin (NTG) on short-term outcomes in ischemic stroke patients remains unclear. This study aimed to evaluate the association between NTG use—including route, timing, and duration—and 28-day in-hospital mortality.MethodsWe conducted a retrospective cohort study of 3,434 ischemic stroke patients, including 356 who received NTG. Propensity score matching (1:1) was used to reduce confounding. Cox proportional hazards models, Kaplan–Meier analysis, and stratified analyses assessed the association between NTG use and mortality.ResultsNTG use was associated with reduced 28-day mortality before (HR = 0.52, p < 0.001) and after matching (HR = 0.50, p = 0.003). Kaplan–Meier curves confirmed this benefit. Among administration routes, only intravenous drip (IV) was significantly associated with reduced mortality (p < 0.001). Early initiation within 24 h (p < 0.001) and a treatment duration of 1–3 days (p < 0.001) were also significantly associated with lower mortality. No benefit was observed for other routes, delayed initiation, or longer durations. Dose-stratified analysis showed no difference between low and high doses (p = 0.59).ConclusionIntravenous drip NTG, started within 24 h and continued for 1–3 days, was significantly associated with lower 28-day mortality in ischemic stroke patients. These findings suggest a potential therapeutic window and warrant further prospective validation.